Pengembangan Sistem Informasi Pengelolaan Program Kreativitas Mahasiswa Politeknik Caltex Riau - Satria Perdana Arifin; ibnu surya (Politeknik Caltex Riau, 2022)
One of the efforts to encourage student creativity is to include and participate in the Program Kreativitas Mahasiswa (PKM), Â the Ministry of Education and Culture initiated. Politeknik Caltex Riau (PCR), through the study program and Student Affairs, manages this PKM to encourage students to innovate and be involved in this PKM. However, the ongoing PKM management has not been well documented, so post-PKM activities are not followed up. It is necessary to have an information system that is used as a media for documenting this PKM management. Information System of Program Kreativitas Mahasiswa (SI PKM) was developed using the Software Development Life Cycle (SDLC) approach; the process is carried out from gathering stakeholder needs, business process analysis, model development, and implementation into the program. The resulting information system can provide a recap of PKM activities, monitoring of guidance carried out between students and lecturers, and visualization in the form of a dashboard to see the involvement of students and study programs in PKM. Based on the results of the Blackbox testing that has been carried out, it is concluded that the PKM management information system has been running well. Â